The Role of Notaries in Supporting the Implementation of Online Single Submission (OSS) in Establishing Business Licensing - Najmuddin, Muhammad; Hafidz, Jawade (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. This study aims to analyze: 1) The role of notaries in supporting the implementation of Online Single Submission (OSS) in the licensing process for establishing a business entity in Batam. 2) Obstacles and solutions in the implementation of Online Single Submission (OSS) related to licensing for establishing a business entity in Batam. This type of research is empirical legal research. The approach method in this study is a sociological legal approach. The types of data in this study are primary and secondary data. The data collection method uses interview and literature (study document) techniques. The analysis in this study is prescriptive. The results of the study concluded: 1) The role of notaries in supporting the implementation of Online Single Submission (OSS) in the licensing process for establishing a business entity in Batam, namely as a compiler of authentic deeds of establishment of a business entity, as a legal facilitator, administrative assistant, and a communication bridge between business actors and the OSS system and government agencies. This role includes ensuring formal legality through deeds and ratification from the Ministry of Law and Human Rights, verification of legal data such as KBLI and company structure, and special assistance for MSMEs and foreign investors who often experience obstacles in navigating the OSS and IBOSS systems. In areas with complexity such as Batam, the active and adaptive role of notaries is the key to the success of the digital business licensing process. 2) Obstacles in the implementation of Online Single Submission (OSS) related to business establishment licensing in Batam still face a number of challenges, including the less than optimal integration between the national OSS and local IBOSS, limited human resources and information technology infrastructure, low understanding of business actors regarding digital systems, overlapping authority between BP Batam and the City Government, and minimal socialization and technical training. Solutions to overcome these obstacles include comprehensive system harmonization, increasing institutional and technological capacity, strengthening the role of notaries as official partners for OSS assistance, establishing clear technical regulations related to institutional authority, and massive education programs for business actors. If implemented consistently, OSS in Batam can become a digital licensing model that is efficient and responsive to the needs of areas with special status.Keywords: Business Entity; OSS; Licensing.